2020
DOI: 10.3390/economies8040099
|View full text |Cite
|
Sign up to set email alerts
|

Resource Rents, Human Development and Economic Growth in Sudan

Abstract: This study investigates the relationship between natural resource rents, human development and economic growth in Sudan using co-integration and vector error correction modelling (VECM) over the period 1970–2015. Institutions proved to play a role in determining a difference in whether a country is cured or blessed by resource abundance. In the case of Sudan, no time series data is available on institutional quality and is therefore excluded from the analysis. The role of institutions and macroeconomic policie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 88 publications
(84 reference statements)
4
14
0
1
Order By: Relevance
“…Again, this result is consistent with the The results revealed that reported that there is no nonlinear causality between oil resource rent and economic growth. Thus, the nonlinear Granger causality test provided evidence supporting no nonlinear causal relationship between oil resource rent and economic growth which is consistent with Quixina and Almeida (2014) but inconsistent with Mohamed (2020). This finding might be as a result of the weak asymmetries detected in our data.…”
Section: Robustness Checksupporting
confidence: 83%
See 1 more Smart Citation
“…Again, this result is consistent with the The results revealed that reported that there is no nonlinear causality between oil resource rent and economic growth. Thus, the nonlinear Granger causality test provided evidence supporting no nonlinear causal relationship between oil resource rent and economic growth which is consistent with Quixina and Almeida (2014) but inconsistent with Mohamed (2020). This finding might be as a result of the weak asymmetries detected in our data.…”
Section: Robustness Checksupporting
confidence: 83%
“…In line with the aim of the study, we focus on related studies that examine the relationship between natural resource extraction (oil production specifically) and economic growth. While some studies used the traditional Granger causality approach to examine the causal relationship between oil resource rent and economic growth (Quixina and Almeida, 2014; Apergis et al , 2014; Parvin Hosseini and Tang, 2014), other studies followed the Vector error correction model as estimation strategy to examine the causative relationship between oil resource rent and economic growth (Hamdi and Sbia, 2013; Mohamed, 2020; Ben-Salha et al , 2018). The outcome for these studies that used the Granger causality have been mixed as some studies found a unidirectional causal relationship from oil revenue and non-oil gross domestic product (GDP) (Quixina and Almeida, 2014; Parvin Hosseini and Tang, 2014) while other studies found bidirectional causative relationship between oil production and GDP (Apergis et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…illustrate that natural resources could act as blessings unless the institutional quality and education are not performing to the quality level. In the case of ( Mohamed, 2020 ), the vector error correction approach was used between the 1970–2015 period and revealed that natural resources are blessings to economic growth. However, these natural resources negatively affect education level and health in the study region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…unveil that volatility in the crude oil market prices significantly causes volatility in the agriculture commodity futures of China. Regarding environmental degradation, the recent study of ( Mohamed, 2020 ) illustrates that an increase in oil prices reduces environmental degradation in the oil-importing economies due to a reduction in oil demand and economic and industrial activities. However, this increase in oil prices positively affects environmental degradation in the oil-exporting economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The positioning of this study departs from extant contemporary literature, which has focused on, inter alia, the nexuses between natural resource rents, economic growth and human development (Sinha & Sengupta, 2019;Mohamed, 2020); the challenge of governance in the light of natural resources rents (Fagbemi & Adeoye, 2020); the effect of natural resources on labour shares (Al-Marhubi, 2020); connections between natural resources, institutional quality, indebtedness and manufacturing (Amiri, Samadian, Yahoo & Jamali, 2019;Muhanji, Ojah & Soumaré, 2019); insights into the natural resource curse (Henri, 2019); secession with natural resources (Dhillon, Krishnan, Patnam & Perroni, 2020); how oil wealth affects development in the long term (Cassidy, 2019); intensive and extensive margins of mining and development (Mano, Bhattacharyya& Moradi, 2019) and the nexus between resource discovery and the political fortunes of national leaders (Bhattacharyya & Keller, 2020).…”
Section: Introductionmentioning
confidence: 96%